GENERATION AND COLLECTION OF TOBACCO AEROSOL FOR SHISHA - N. N. Bubnova; M. V. Shkidyuk (Новые технологии, 2020)
Qualitative characteristics of tobacco aerosol for shisha are determined by the functional purpose and depend on the component composition of the tobacco mixture and the coal used.The purpose of the research is to develop a methodology for the comprehensive assessment of tobacco for shisha based on modern methods of product quality control and includes the following steps:- monitoring of the studies to determine the component composition of the hookah mixture and the aerosol produced;- analysis of hookah mixture testing modes and development of an aerosol generation protocol;- development of a method for collecting aerosol on a laboratory smoking machine; - quantitative analysis of toxic analytes by HPLC MS / MS method.Methods have been developed for the machine generation and collection of tobacco aerosol for hookah, taking into account low concentrations of the analyzed toxic substances.The expediency of using the HPLC MS / MS method to determine the quantity of the following substances in tobacco aerosol for shisha has been substantiated:- carbonyl compounds (formaldehyde, acetaldehyde, acrolein) by detection on an electrospray source in the negative polarity mode- tobacco specific nitrosoamines (NNN and NNK) by detection on an electrospray source in the positive polarity mode.During the research laboratory and analytical equipment was used: a five-channel linear CERULEAN SM 405 smoking machine; Thermo Scientific Dionex UltiMate 3000 liquid chromatograph and TSQ Quantiva mass spectrometer.Obtaining experimental data on the quantitative determination of the component composition of the aerosol produced by tobacco for shisha using hookah systems is relevant for assessing toxic characteristics of the product.